A Literature Study on Science Learning Media in Elementary School - Fika Ari Widyaningrum; Ika Maryani; Rungchatchadaporn Vehachart (International Journal of Learning Reformation in Elementary Education, 2022)
This study aims to discover the development of research on elementary science learning media in 2017-2021 and find future research opportunities in elementary science learning media. The type of research used is descriptive quantitative using bibliometric analysis assisted by VOSviewer and Mendeley software. This research data is in the form of 111 research journal articles on elementary science learning media conducted in Indonesia and sourced from several SINTA 1-6 journals in the 2017-2021 timeframe. From the study results, the development of research on elementary science learning media was the highest in 2018. Opportunities for learning media research topics can still be done by selecting keywords rarely used by previous researchers, namely training, science abstract, learning independence, science process skills, cartoons, flashcards, index card matches, puzzles, mastery of concepts, and monopoly games. You can also choose topics with the latest discussion trends using articulate storyline keywords, media development, STEM-based science learning, 21st century, Canva, application of learning media, wonder share, software, mobile learning, monopoly games, mastery of concepts, en-alter source, animation, online, discovery learning, interest and learning outcomes, animated videos, and development models.